Polynomial reconstruction of the matching polynomial - Xueliang Li; Yongtang Shi; Martin Trinks (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2015)
The matching polynomial of a graph is the generating function of the numbers of its matchings with respect to their cardinality. A graph polynomial is polynomial reconstructible, if its value for a graph can be determined from its values for the vertex-deleted subgraphs of the same graph. This note discusses the polynomial reconstructibility of the matching polynomial. We collect previous results, prove it for graphs with pendant edges and disprove it for some graphs.